Implications of Globalization for Monetary Policy - Wagner, Helmut (IMF Working Papers; Working Paper ;, 2001)
This paper argues that the implications of globalization for monetary policy come mainly through two channels: On the one hand, the many structural changes that are associated with the globalization process cause an increase in the uncertainty surrounding monetary policy. This includes an increase in uncertainty about how to interpret macroeconomic data/indicators and about the monetary transmission mechanism. On the other hand, by strengthening the process of global economic integration, globalization increases international competition, thereby forcing market players to make structural adjustments or reforms that change the conditions or constraints under which monetary policy is implemented.